2021
DOI: 10.1159/000515302
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Efficacy of Atezolizumab plus Bevacizumab and Other Treatment Options for Patients with Unresectable Hepatocellular Carcinoma: A Network Meta-Analysis

Abstract: <b><i>Background:</i></b> Most phase 3 clinical trials of systemic therapy for first-line unresectable hepatocellular carcinoma (HCC) have failed, with the exception of SHARP, REFLECT, and IMbrave150. We conducted indirect comparisons of therapies evaluated for first-line HCC treatment. <b><i>Summary:</i></b> We conducted a systematic review and meta-analysis of treatments for adults with locally advanced or metastatic unresectable HCC and no prior systemic treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
42
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 20 publications
4
42
0
2
Order By: Relevance
“…However, we did not include their findings in the Technical Review due to the overall very low to low CoE in the trials that provided direct comparisons. [32][33][34][35][36][37][38]…”
Section: Other Agentsmentioning
confidence: 99%
“…However, we did not include their findings in the Technical Review due to the overall very low to low CoE in the trials that provided direct comparisons. [32][33][34][35][36][37][38]…”
Section: Other Agentsmentioning
confidence: 99%
“…First, the included trials presented heterogeneous study design, and the statistics quantifying the NMA heterogeneity were not reported. Second, although the authors reported that risk of bias was generally low across trials, lack of study blinding in 7 of 9 trials raises concerns, and in addition, risk of bias could not be assessed for CheckMate 459 [4]. Third, if certainly Bayesian NMA represents a powerful method that allows the sharing of information across different clinical trials, cross-trial comparisons may only partially compare adverse events and safety profiles [5].…”
Section: Dear Editormentioning
confidence: 99%
“…Atezolizumab-bevacizumab has become the new benchmark for front-line treatment in unresectable HCC [1][2][3][4]; on the horizon, there is a host of phase III randomized clinical trials of novel combinations including immune checkpoint inhibitors combined with other antiangiogenic agents as well as PD-1 or PD-L1 inhibitors plus CTLA-4 inhibitors. The results of these studies are highly awaited and have the potential to further modify the first-line treatment scenario of this challenging malignancy.…”
Section: Dear Editormentioning
confidence: 99%
See 2 more Smart Citations